Narasi militer dalam buku teks pelajaran Sejarah Indonesia SMA kelas XII - Shilvi Khusna Dilla Agatta; Kasimanuddin Ismain; Ronal Ridhoi (Universitas Negeri Malang, 2022)
Textbooks are media that play an important role in learning activities in the classroom. In this research, the textbook that used the object of research was the Indonesian History Textbook for SMA Class XII, especially the military narrative on the material of the struggle to national disintegration. However, there are narratives that have words or sentences that can show understanding of multiple interpretations. Therefore, the purpose of this research is to analyze the discourse in the textbook on military narratives so that they can be understood and avoid negative perspectives. So the method uses critical discourse analysis of the Teun A. van Dijk model, which includes three structures are macrostructure, superstructure, and microstructure to see word choice and sentence structure in military narration in textbooks. This research by using a qualitative design with text analysis methods and literature/document studies as data collection methods. The result shows that the military narrative is shown as the central figure who defends the country.